Interactive Learning Media Application About Animal Recognition Using the Computer Assisted Instruction (CAI) Method at PAUD KB Sakinah - Nopita Eliansari; Harianja Harianja (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2023)
Learning Media in general is a tool in the teaching and learning process. The use of computers as a learning medium or known as CAI (Computer Assisted Instruction) is a microprocessor-based learning material delivery system whose lessons are designed and programmed into the system. This can be an innovative learning tool compared to blackboards and chalk. SAKINAH KB PAUD is an early childhood education located in Baru Ibul village. The learning media currently used at PAUD KB SAKINAH for introducing animals is using Origami paper as a visual tool. The aim of this research is to create a more interesting and interactive animal recognition learning media application to make it easier for teachers in the teaching and learning process. The method used in this research is the Waterfall method (sequentially) which consists of six stages, namely requirements (needs analysis), system design (system design), coding (coding), testing (testing) and operation & Mintence (maintenance). This research resulted in an interactive learning media application for animal recognition at PAUD KB SAKINAH.